MODEL OF THE TACTICAL AIRCRAFT OPERATING SYSTEM AS AN AGGREGATED ANALYSIS DOMAIN FOR HAZARD RISK MANAGEMENT PROCESSES - Emil AUGUSTYN; Adam KADZIŃSKI; Piotr SMOCZYŃSKI (Scientific Journal of Silesian University of Technology. Series Transport)
The Tactical Aircraft Operating System (a system for tactical aircraft operational usage) constitutes the main research area of this paper. The authors present this system via an innovative model for an anthropotechnical system in the format of an aggregated analysis domain. This model constitutes a detailed explication of a fragment of the existing Tactical Air Force System metamodel at the level that concerns tactical aircraft operation systems. The aggregated analysis domain for tactical aircraft operations is built on seven single-analysis domain, each of which includes a series of processes, operations and events, related to the airman’s aviation activities cycle, what happens during an air mission and when an aircraft operating cycle is carried out. The subsequent individual analysis domains are connected to each other by an airman-aircraft anthropotechnical pair. The introduced method of modelling the Tactical Aircraft Operating System ensures the desired generality, comprehensiveness, coherence and transparency of such a model, which allows for its implementation in various types of tactical aircraft and tactical air force bases. In principle, within the presented considerations, the model is described in relation to a single aircraft operating cycle, which is carried out by one airman during a single air mission. However, the authors have taken care when creating this model structure, so that its implementation in more complex aircraft operating cycles (more than one aircraft and one airman) is possible. Apart from the analysis domains (“before take-off”, “departure”, “air task”, “arrival”, “after landing”), which are closely related to the essential aircraft operations, the model also includes the analysis domains associated with air mission preparations and summaries. The model for the Tactical Aircraft Operating System is described by the authors in textual form, as well as in tabular form. The presented concept constitutes an attempt to formally notate the Tactical Aircraft Operating System model, in which each of the individual analysis domains can be treated as an area of interest for hazard risk management processes within the Tactical Air Force System.